(untitled) (Proceedings of International Conference on Special Education, 2025)
Autism Spectrum Disorder (ASD) is characterized by distinct neurological and behavioural traits that can influence learning adaptation and social interaction. Understanding autistic traits (ATs) in structured educational settings such as boarding schools, is crucial for developing effective support strategies. This study provides a descriptive analysis of ATs patterns among boarding school students in Malaysia using the translated Malay version of the Autism Quotient Short (AQ-28). A total of 966 students from various boarding schools across Peninsular Malaysia participated in the study. The findings revealed a mean AQ-28 score of 62.66 (SD = 6.94), indicating varying levels of ATs among students. The descriptive analysis highlights notable patterns in ATs distribution, suggesting that autistic characteristics may influence students’ academic engagement, peer relationships and overall adaptation to the boarding school environment. Given the structured and socially immersive nature of boarding schools, students with higher ATs levels may face unique challenges in both academic and social contexts. These findings underscore the importance of implementing inclusive educational practices such as differentiated instruction, social skills development and tailored support systems to enhance student well-being. By providing a comprehensive overview of ATs prevalence, this study contributes to a deeper understanding of neurodiversity in Malaysian boarding schools and informs proactive educational strategies. Recognizing and addressing the diverse needs of students with ATs can help create a more supportive and inclusive learning environment. Overall, giving them the opportunity to grow academically, socially and emotionally, it will help to increase their self-confidence, motivation to learn, and their interaction skills in the school community and society.